# 7x-(-13+3x)12=13

## Simple and best practice solution for 7x-(-13+3x)12=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 7x-(-13+3x)12=13 equation:

Simplifying
7x + -1(-13 + 3x) * 12 = 13
Reorder the terms for easier multiplication:
7x + -1 * 12(-13 + 3x) = 13
Multiply -1 * 12
7x + -12(-13 + 3x) = 13
7x + (-13 * -12 + 3x * -12) = 13
7x + (156 + -36x) = 13
Reorder the terms:
156 + 7x + -36x = 13
Combine like terms: 7x + -36x = -29x
156 + -29x = 13
Solving
156 + -29x = 13
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-156' to each side of the equation.
156 + -156 + -29x = 13 + -156
Combine like terms: 156 + -156 = 0
0 + -29x = 13 + -156
-29x = 13 + -156
Combine like terms: 13 + -156 = -143
-29x = -143
Divide each side by '-29'.
x = 4.931034483
Simplifying
x = 4.931034483`